2010
DOI: 10.1021/nl101944e
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Water Sterilization Using One-Dimensional Nanostructures

Abstract: The removal of bacteria and other organisms from water is an extremely important process, not only for drinking and sanitation but also industrially as biofouling is a commonplace and serious problem. We here present a textile based multiscale device for the high speed electrical sterilization of water using silver nanowires, carbon nanotubes, and cotton. This approach, which combines several materials spanning three very different length scales with simple dying based fabrication, makes a gravity fed device o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 31 publications
2
122
0
Order By: Relevance
“…Two major elements in the Ag 2−x (NH 4 ) x Mo 3 O 10 ·3H 2 O nanowires are expected to have the antibacterial nature, that is, the Ag + ions and the Mo 6+ ions of the composite, both of which have been reported previously [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][41][42][43]. In this work, we have also observed a large amount of Ag-rich nanoparticles on surface of the nanowires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two major elements in the Ag 2−x (NH 4 ) x Mo 3 O 10 ·3H 2 O nanowires are expected to have the antibacterial nature, that is, the Ag + ions and the Mo 6+ ions of the composite, both of which have been reported previously [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][41][42][43]. In this work, we have also observed a large amount of Ag-rich nanoparticles on surface of the nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, with a high surface-to-volume ratio, Ag nanoparticles showed much higher antimicrobial efficiency than Ag microparticles [8][9][10][11][12][13][14][15][16]. In some biological applications, it should be rather interesting if Ag composites or nanoparticles could be delivered to target tissues and/or cells with a controllable carrier of nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial effects of Ag-based NWs (Holtz et al 2010(Holtz et al , 2012Jiang et al 2012;Liu et al 2013;Schoen et al 2010;Singh et al 2014;Tamboli et al 2012;Tang et al 2014;Visnapuu et al 2013;Zhang et al 2007), Si NWs (Lv et al 2010), ZnO NWs (Kılıç and Omay 2014;Wu et al 2011), MgO NWs (AlHazmi et al 2012, Mn 2 O 3 NWs (Hassan et al 2012), Tibased NWs (Nataraj et al 2014;Shang et al 2010), and CdO NWs (Kumar and Ojha 2013) were evaluated. Test subjects included the pathogenic bacteria species Escherichia coli, Bacillus subtilis, Staphylococcus aureus, …”
Section: Toxicity Of Nanowires To Bacteriamentioning
confidence: 99%
“…In recent years, antimicrobial materials are also incorporated into air filter to inhibit the growth of collected microorganisms (Foarde et al 2000;Cecchini et al 2004;Lee et al 2008a). The filtration technologies developed using nanoscale materials for water treatments (Brady-Estevez et al 2010;Schoen et al 2010) can certainly be adapted for airborne microbial aerosol control. In a recent study, carbon nanotubebased filters were applied to controlling bioaerosols, and the results indicated that a physical removal efficiency of 95% was obtained for B. subtilis var niger at a carbon nanotube loading of 1.6 µg/cm 2 (Guan and Yao 2010).…”
Section: Bioaerosol Control and Inactivationmentioning
confidence: 99%